(untitled) (مجلة المنصور, 2022)
This paper present mobile social media application planned for high scholars clients “teenager” in place to forestall what’s more relieve mean and brutal conduct behavior on the web. The reason for those suggested application is to make a disparaging place environment where teens use an assortment of offers planned on help raise self-awareness of their own web behavior, look for support at needed, and take in should control and right aggressive behavior. The proposed design plan will be outline by four principles: design plan for Reversal, design plan for sympathy, design plan to Authorization, and design plan for those whole. We end by plotting more add-ons our provision on make it serves to enhance the web encounters for teens. The application effort need suggestive for the group of health on account to apply answers for tackle a critical social issue that could influence the wellbeing the health and prosperity about teens. Toward utilizing this application, our pushed should make a nurturing environment, develop beneficial on the online web behavior, also ultimately, relieve and keep mean and sever behavior online.